IDENTIFIKASI PENCEMARAN AIRTANAH DI DESA DALEMAN - COKRO, DAN SEKITARNYA, KECAMATAN TULUNG, KABUPATEN KLATEN, PROVINSI JAWA TENGAH - , HASTOMO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Daleman - Cokro village, District Tulung , Klaten Regency is an area that has good groundwater potential . But with the center of the palm flour industry is growing rapidly, the potential danger of groundwater pollution affected due to the waste dumped by the industrial activity. The results are useful for the identification of groundwater pollution (1) analyzing the hydrogeological conditions of research areas, (2) groundwater flow model to determine the groundwater flow pattern study area, (3) identify the types of pollutants and levels of contaminants in wastewater and groundwater sources around the sugar processing industry, and ( 4 ) predict the pattern of the spread of contaminants in the groundwater in the study area. The first stage in identifying groundwater contamination groundwater advance height measurement to determine the pattern of groundwater flow in the study area and geological mapping to determine the hydrogeological conditions of the study area, groundwater sampling and laboratory testing of chemical parameters nitrate , phenol , chloride , total oil and organic matter ( COD and BOD ) to identify the types and levels of contaminants both on the water and the waste water well. Identification results obtained that the pollutants are present in the waste is organic matter and total oil quality standard based on comparison with the Indonesian Government Regulation No. 82 of 2001 and as for the sources of groundwater contaminants are present, namely nitrate, based on a comparison of standard quality regulation Health of the Republic of Indonesia Number 492/MENKES/PER/IV/2010. The movement of pollutants can be predicted by using two concepts , namely modeling with the help of software Visual MODFLOW and distribution of chloride concentration. Pollutants are expected to follow the movement of groundwater flow moving east - west .